'No problem' advice during occupational health examinations. (15th January 2021) - Weiste, Elina; Leino, Timo; Laitinen, Jaana
Abstract : In many countries, occupational health examinations are considered to have a central role in ensuring that employees' health and work ability are maintained or enhanced. In contemporary Finland, the institutional goal of these examinations is to construct a health plan based on the client's own aims, and in this paper we analyse how occupational health nurses and clients in Finland negotiate what is considered to be a problem. The data consist of 10 video-recorded occupational health examination encounters, analysed by means of conversation analysis. Our analysis focuses on 'no problem' advice, in which the advice giving is initiated in the absence of a problem-indicative response. The client's 'no problem' response was typically followed by the nurse upgrading the problem that she had identified and giving a general reminder of a possible problem. The clients resisted not so much the content of the advice, but the act of advising itself. In a few cases, the client's 'no problem' response was followed by a turn in which the nurse contested the client's knowledge and offered advice that was tailored to the client's situation. The client acknowledged the advice as new information. Our findings indicate that regardless of client-centred ideals, the interaction in occupational health examinations is largely led by nurses, who set up the agenda and raise issues that they consider to be problems for their clients.